Positive and Negative Face Threatening Acts on Family and School Interaction of “No Place Strange” Novel by Diana Fitzgerald Bryden: Lingguistic - Okky Ria Vinola; Sulistyaningsih Sulistyaningsih; Kani Sulam Taufik (International Journal of English and Applied Linguistics (IJEAL), 2023)
The objectives of this research are find the Face Threatening Acts (FTAs) in Diana Fitzgerald Bryden novel by the title No Place Strange. The aim of this study were to find the kinds of Face Threatening Acts that were produced by character in No Place Strange novel. This research applied to descriptive qualitative where the data were analyzed by Brown and Levinson theory. Based on the analysis in this research, the researcher found Face Threatening Acts in the Novel No Place Strange that there are 17 utterances which showed 13 Negative face threatening acts and 4 Positive face threatening acts that employed by the interaction in the family and school. Based on the finding above, the researcher concluded that the utterances more dominant used in that novel are Negative face threatening acts than Positive face threatening acts.